Picture Exchange Communication System for Individuals with Autism Spectrum Disorder - Andersen, Lauren E. (Journal of the American Academy of Special Education Professionals, 2010)
Autism spectrum disorder (ASD) is a neurological disorder that manifests itself within an individual through cognitive, social, and academic deficits. As is true for all spectrum disorders, each individual may experience a range of deficits with varying severity. Many students with autism spectrum disorder experience difficulty in some area of communication. The Picture Exchange Communication System (PECS) was developed in an effort to remedy the communication difficulties between individuals with severe ASD and their peers. The main goal of PECS is to enable students with communication deficits to spontaneously communicate with their peers. The system is composed of six different phases in which a student may progress with increasing independency. While many individuals with ASD are able to communicate effectively with PECS, such a system is not suitable for all individuals on the spectrum; therefore, it is imperative for professionals, parents, and peers to be knowledgeable of the implementation, utilization, and culmination of the Picture Exchange Communication System.